P422 Immunogenicity of a proposed adalimumab biosimilar, FKB327, and the reference product in patients with rheumatoid arthritis. (25th January 2019) - Alten, R; Markland, C; Kawakami, K; Boyce, M; Casty, F; Muniz, R; Genovese, M C
Abstract: Background: The FKB327-002 double-blind (DB) study to compare the efficacy and safety of a candidate adalimumab biosimilar, FKB327, and the reference product (RP) in patients with rheumatoid arthritis also being treated with methotrexate (MTX)—the ARABESC trial—was presented previously. The FKB327-003 study, also known as the ARABESC-OLE trial, was a Phase 3 open-label extension (OLE) study to compare the long-term safety, efficacy, immunogenicity, and pharmacokinetics of FKB327 and RP. The immunogenicity of RP and FKB327 was examined across studies. Methods: In the DB study, patients were randomised 1:1 to receive FKB327 or RP (40 mg subcutaneously) every other week for 24 weeks, with continuing MTX. In the OLE study, patients completing the DB study with clinical response and no safety concerns were immediately re-randomised to FKB327 or RP, so that two-thirds of patients remained on the same treatment as in the DB study and one-third switched to the alternate treatment for weeks 0 through 28 (Part 1), then all received FKB327 through Week 78 (Part 2). A total of 645 patients (FKB327, n = 324; RP, n = 321) who entered the OLE study were evaluated for immunogenicity during continuous treatment and across switching sequences in the studies. Immunogenicity was assessed by evaluation of antidrug antibodies (ADAs; proportion of patients ADA-positive, ADA-titre, and neutralising ADAs) using validated, high-sensitivity electrochemiluminescence assay and competitive ligand-binding assay. The impact of ADAs on efficacy and safety was also evaluated. Results: The proportion of patients with positive ADA status was highest prior to dosing at week 0 in the OLE study, at 61.7% and 60.0% for FKB327 and RP, respectively. The proportion of patients with positive ADA status did not increase over time to Week 30 (the end of Part 1) and was similar for FKB327 and RP at all time points. The majority of ADAs were neutralising. At Week 78, the proportion of patients with positive ADA status was lower in all treatment sequences, at 51.1%, 54.4%, 48.1%, and 42.5% for the FKB327–FKB327–FKB327, FKB327–RP–FKB327, RP–FKB327–FKB327, and RP–RP– FKB327 treatment sequences, respectively. The scale of negative impact of ADA on efficacy was higher in the ADA high-titre category in FKB327 and RP to a similar degree. Incidence of hypersensitivity and injection-site reactions was low in both FKB327 and RP, with no apparent relationship to ADA-titre category. Conclusions: The RP and FKB327 showed comparable immunogenicity in long-term administration. Treatment switching from RP to FKB327 or vice versa did not influence either immunogenicity or sustainability of efficacy or safety.